2014
DOI: 10.1111/1471-0307.12145
|View full text |Cite
|
Sign up to set email alerts
|

Combined milk gel generated with a novel coagulating enzyme by Virgibacillus sp. SK37, a moderately halophilic bacterium

Abstract: The hydrolysis of milk proteins by the recombinant AprX-SK37 protease and the changes in the rheological properties of the milk gel generated with AprX-SK37 and glucono-d-lactone (GDL) were investigated. The AprX-SK37 and rennet selectively hydrolysed j-casein to yield a 16-kDa band, while subtilisin hydrolysed all of the casein components. Milk treated only with AprX-SK37 formed softer gel. Storage modulus (G 0 ) values of the combined gels increased with GDL concentrations up to 7 g/L. High tan d was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The maximum MCA was observed at pH 5.0. The activity decreased at higher pH which might be due to the stability of casein micelles at high pH which led to a decrease in MCA [ 35 ]. Many authors have also observed a drop in MCA at high pH values [ 11 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum MCA was observed at pH 5.0. The activity decreased at higher pH which might be due to the stability of casein micelles at high pH which led to a decrease in MCA [ 35 ]. Many authors have also observed a drop in MCA at high pH values [ 11 , 36 ].…”
Section: Discussionmentioning
confidence: 99%